Effects of (±) 3,4-Methylenedioxymethamphetamine (MDMA) on Sleep and Circadian Rhythms - Una D. McCann; George A. Ricaurte (The Scientific World Journal)
Abuse of stimulant drugs invariably leads to a disruption in sleep-wake patterns by virtue of the arousing and sleep-preventing effects of these drugs. Certain stimulants, such as 3,4-methylenedioxymethamphetamine (MDMA), may also have the potential to produce persistent alterations in circadian regulation and sleep because they can be neurotoxic toward brain monoaminergic neurons involved in normal sleep regulation. In particular, MDMA has been found to damage brain serotonin (5-HT) neurons in a variety of animal species, including nonhuman primates, with growing evidence that humans are also susceptible to MDMA-induced brain 5-HT neurotoxicity. 5-HT is an important modulator of sleep and circadian rhythms and, therefore, individuals who sustain MDMA-induced 5-HT neurotoxicity may be at risk for developing chronic abnormalities in sleep and circadian patterns. In turn, such abnormalities could play a significant role in other alterations reported in abstinent in MDMA users (e.g., memory disturbance). This paper will review preclinical and clinical studies that have explored the effects of prior MDMA exposure on sleep, circadian activity, and the circadian pacemaker, and will highlight current gaps in knowledge and suggest areas for future research.